STRATEGI KOMUNIKASI AREA MANAGER JAWA TENGAH DALAM MENINGKATKAN KNERJA AGENT RELATIONSHIP OFFICER OTO.COM CABANG SOLO - Maharani, Adisty Permata; Mahar Rizqi, Fikriana (Solidaritas, 2024)
This research was motivated by the decline in sales experienced by Oto.com Solo Branch, so that the targets that had been determined could not be achieved optimally. After tracing the factors, the decline in sales was caused by the decline in the performance of the Oto.com Solo Branch Agent Relationship, which was triggered by miscommunication that occurred between the Branch Manager and the Solo Branch Agent Relationship Officer. As the highest authority in the Central Java area, the Area Manager has an obligation to resolve problems. Therefore, the right strategy is needed so that the problem can be resolved appropriately. This research uses a qualitative descriptive method, with interview and documentation data collection techniques. The research results show that the communication strategy implemented by the Area Manager is knowing the audience, compiling messages, determining and using media. Keyword: Communication strategy, Performance, Area Manager